Prediction of rock fracture toughness modes I and II utilising brittleness indexes. (2012) - Saeidi, O.; Torabi, S.R.; Ataei, M.; Hoseinie, S.H.
Fracture toughness and brittleness are of the most crucial rock features for underground excavation and drilling in rock mass. Developed standard tests to determine rock fracture toughness are very difficult as well as time consuming; furthermore, they require high-level accuracy during sample preparation and testing. An attempt has been made to propose simple relations to determine fracture toughness modes I and II based on brittleness indexes B 1, B 2 and B 3 in this paper. The data for regression were gathered from the literature, including modes I and II fracture toughness, uniaxial compressive strength and tensile strength. It was obtained that both fracture toughness modes I and II of different rock types give reasonable correlations with brittleness index B 1 . No correlation was observed between fracture toughness modes and other brittleness indexes.